Isparta’nın 1950 Sonrası Çağdaş Yapıları - Güvlü Erhan, Gizem; Çelebi Gürkan, Ülkü; Akyol, Gamze; Çelebi Karakök, M. Elif; Tuncer Pürselim, Hilal; Büyükemir Karagöz, Esra; Sümer Haydararslan, Kübra (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-